The Efficacy of Mizoribine (Inosine Monophosphate Dehydrogenase Inhibitor) for ANCA-Associated Vasculitis with Hepatitis B Virus Carrier - Jun Muratsu; Atsuyuki Morishima; Masayoshi Kukida; Anzu Tanaka; Shigeki Fujita; Katsuhiko Sakaguchi (Case Reports in Immunology)
A 42-year-old female who was an asymptomatic carrier of hepatitis B virus (HBV) was diagnosed with antineutrophil cytoplasm antibody- (ANCA-) associated vasculitis and was induced to remission with 30 mg/day prednisolone nine years ago. Four years ago, she suffered recurrence of ANCA-associated vasculitis and with 30 mg/day prednisolone was induced to remission. This time, laboratory data showed 3-fold increase in myeloperoxidase antineutrophil cytoplasmic antibody (MPO-ANCA) levels. Administration of 30 mg/day prednisolone was started. Three days later, she was admitted to our hospital suffering from fatigue. After admission, urinalysis showed glomerular hematuria. Despite administration of 30 mg/day prednisolone, MPO-ANCA titer had been of high level, ranging from 42 to 83 EU for 2.5 months. Furthermore, the adverse effects of steroid were seen. We decided the tapering of prednisolone (25 mg/day) and the start of mizoribine (4-carbamoyl-1-β-D-ribofuranosyl imidazolium-5-olate) administration. After mizoribine treatment, MPO-ANCA titer was decreased without any mizoribine-related adverse effects. Six months later, MPO-ANCA titer was decreased to normal levels and she was induced to clinical remission without reactivation of HBV. We describe the effectiveness of mizoribine for the ANCA-associated vasculitis complicated with HBV-carrier.